Genetics of schizophrenia in the South African Xhosa. - Gulsuner, S; Stein, D J; Susser, E S; Sibeko, G; Pretorius, A; Walsh, T; Majara, L; Mndini, M M; Mqulwana, S G; Ntola, O A; Casadei, S; Ngqengelele, L L; et al. (Science, 2020)
Africa, the ancestral home of all modern humans, is the most informative continent for understanding the human genome and its contribution to complex disease. To better understand the genetics of schizophrenia, we studied the illness in the Xhosa population of South Africa, recruiting 909 cases and 917 age-, gender-, and residence-matched controls. Individuals with schizophrenia were significantly more likely than controls to harbor private, severely damaging mutations in genes that are critical to synaptic function, including neural circuitry mediated by the neurotransmitters glutamine, γ-aminobutyric acid, and dopamine. Schizophrenia is genetically highly heterogeneous, involving severe ultrarare mutations in genes that are critical to synaptic plasticity. The depth of genetic variation in Africa revealed this relationship with a moderate sample size and informed our understanding of the genetics of schizophrenia worldwide.
Keywords: Age Factors; Autistic Disorder; Bipolar Disorder; Dopamine; Female; gamma-Aminobutyric Acid; Genetic Variation; Glutamine; Humans; Male; Mutation; Neural Pathways; Schizophrenia; Sex Factors; South Africa; Synapses; Synaptic Transmission

The impact of sex on gene expression across human tissues. - Oliva, Meritxell; Muñoz-Aguirre, Manuel; Kim-Hellmuth, Sarah; Wucher, Valentin; Gewirtz, Ariel D H; Cotter, Daniel J; Parsana, Princy; Kasela, Silva; Balliu, Brunilda; Viñuela, Ana; Castel, Stephane E; Mohammadi, Pejman; et al. (Science, 2020)
Many complex human phenotypes exhibit sex-differentiated characteristics. However, the molecular mechanisms underlying these differences remain largely unknown. We generated a catalog of sex differences in gene expression and in the genetic regulation of gene expression across 44 human tissue sources surveyed by the Genotype-Tissue Expression project (GTEx, v8 release). We demonstrate that sex influences gene expression levels and cellular composition of tissue samples across the human body. A total of 37% of all genes exhibit sex-biased expression in at least one tissue. We identify cis expression quantitative trait loci (eQTLs) with sex-differentiated effects and characterize their cellular origin. By integrating sex-biased eQTLs with genome-wide association study data, we identify 58 gene-trait associations that are driven by genetic regulation of gene expression in a single sex. These findings provide an extensive characterization of sex differences in the human transcriptome and its genetic regulation.
Keywords: Chromosomes, Human, X; Disease; Epigenesis, Genetic; Female; Gene Expression; Gene Expression Regulation; Genetic Variation; Genome-Wide Association Study; Humans; Male; Organ Specificity; Promoter Regions, Genetic; Quantitative Trait Loci; Sex Characteristics; Sex Factors

Large-Scale Exome Sequencing Study Implicates Both Developmental and Functional Changes in the Neurobiology of Autism. - Satterstrom, F Kyle; Kosmicki, Jack A; Wang, Jiebiao; Breen, Michael S; De Rubeis, Silvia; An, Joon-Yong; Peng, Minshi; Collins, Ryan; Grove, Jakob; Klei, Lambertus; Stevens, Christine; Reichert, Jennifer; et al. (Cell, 2020)
We present the largest exome sequencing study of autism spectrum disorder (ASD) to date (n = 35,584 total samples, 11,986 with ASD). Using an enhanced analytical framework to integrate de novo and case-control rare variation, we identify 102 risk genes at a false discovery rate of 0.1 or less. Of these genes, 49 show higher frequencies of disruptive de novo variants in individuals ascertained to have severe neurodevelopmental delay, whereas 53 show higher frequencies in individuals ascertained to have ASD; comparing ASD cases with mutations in these groups reveals phenotypic differences. Expressed early in brain development, most risk genes have roles in regulation of gene expression or neuronal communication (i.e., mutations effect neurodevelopmental and neurophysiological changes), and 13 fall within loci recurrently hit by copy number variants. In cells from the human cortex, expression of risk genes is enriched in excitatory and inhibitory neuronal lineages, consistent with multiple paths to an excitatory-inhibitory imbalance underlying ASD.
Keywords: Autistic Disorder; Case-Control Studies; Cell Lineage; Cerebral Cortex; Cohort Studies; Exome; Female; Gene Expression Regulation, Developmental; Gene Frequency; Genetic Predisposition to Disease; Humans; Male; Mutation, Missense; Neurobiology; Neurons; Phenotype; Sex Factors; Single-Cell Analysis; Whole Exome Sequencing

Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome. - Hijazi, Hadia; Coelho, Fernanda S; Gonzaga-Jauregui, Claudia; Bernardini, Laura; Mar, Soe S; Manning, Melanie A; Hanson-Kahn, Andrea; Naidu, Sakkubai; Srivastava, Siddharth; Lee, Jennifer A; Jones, Julie R; Friez, Michael J; et al. (Hum Mutat, 2020)
Xq22 deletions that encompass PLP1 (Xq22-PLP1-DEL) are notable for variable expressivity of neurological disease traits in females ranging from a mild late-onset form of spastic paraplegia type 2 (MIM# 312920), sometimes associated with skewed X-inactivation, to an early-onset neurological disease trait (EONDT) of severe developmental delay, intellectual disability, and behavioral abnormalities. Size and gene content of Xq22-PLP1-DEL vary and were proposed as potential molecular etiologies underlying variable expressivity in carrier females where two smallest regions of overlap (SROs) were suggested to influence disease. We ascertained a cohort of eight unrelated patients harboring Xq22-PLP1-DEL and performed high-density array comparative genomic hybridization and breakpoint-junction sequencing. Molecular characterization of Xq22-PLP1-DEL from 17 cases (eight herein and nine published) revealed an overrepresentation of breakpoints that reside within repeats (11/17, ~65%) and the clustering of ~47% of proximal breakpoints in a genomic instability hotspot with characteristic non-B DNA density. These findings implicate a potential role for genomic architecture in stimulating the formation of Xq22-PLP1-DEL. The correlation of Xq22-PLP1-DEL gene content with neurological disease trait in female cases enabled refinement of the associated SROs to a single genomic interval containing six genes. Our data support the hypothesis that genes contiguous to PLP1 contribute to EONDT.
Keywords: Child; Child, Preschool; Chromosome Breakpoints; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, X; Comparative Genomic Hybridization; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Nervous System Diseases; Pedigree; Phenotype; Quantitative Trait, Heritable; Repetitive Sequences, Nucleic Acid; Sex Factors; Syndrome; X Chromosome Inactivation